Gas chromatography/mass spectrometry analysis of components of pyridine temperature-programmed desorption spectra from surface of copper-supported catalysts - Přibylová, Lenka; Dvořák, Bohumír (Journal of chromatography. A, Including electrophoresis and other separation methods, 2009)
The method of pyridine temperature-programmed desorption (TPD) was applied for the measurement of acid properties of in situ reduced copper catalysts on silicate support. A thermal-conductivity detector (TCD) was used for the detection of TPD spectra of pyridine. The combination of flame-ionization detector and thermal conductivity detector shows that the region of TPD spectrum with the peak maxima T(MAX1)=350 degrees C is a superposition of the TCD response on spectra of desorbed pyridine, water and carbon dioxide, desorbing simultaneously from the catalyst surface. The method for the elimination of H(2)O and CO(2) on the layer of NaOH was tested and the pure TPD spectrum of pyridine was obtained. The exact determination of pyridine concentration allows to estimate the amount of weak and medium acid centers of the catalyst. The gas chromatography with the mass spectroscopy (GC-MS) analyses was used for the interpretation of high temperature region of the pyridine TPD spectra (T(MAX2)=620 degrees C). It was found that pyridine bonded on the strong acid centers is decomposed to N(2) and CO under very high temperature. The available chromatographic method for the separation of components present in pyridine TPD spectrum in the high-temperature region was suggested. The method for the quantification of strong acidity of copper-supported catalyst was found.
Keywords: Adsorption; Copper; Gas Chromatography-Mass Spectrometry; Pyridines; pyridiny; Catalysis; Temperature; plynová chromatografie s hmotnostně spektrometrickou detekcí; teplota; katalýza; adsorpce; měď